Engineered Prx-LCA2 fusion protein restores oxidative skin damage via enhanced intracellular peroxidase delivery - Di Liu; Yafen Zhan; Jiaqi Qu; Hongping Qiao; Na Li; Yeli Zhang; Xiaoying Wu (AMB Express)
Abstract This study developed a novel antioxidant fusion protein Prx-LCA2 by conjugating peroxidase Prx with the LCA2 carrier derived from Escherichia coli heat-labile enterotoxin, aiming to achieve efficient intracellular delivery for oxidative damage remediation. The fusion protein Prx-LCA2 was successfully expressed in E. coli and purified. Fluorescence labeling demonstrated efficient cellular internalization of the fusion protein. In vitro, H2O2-induced oxidative stress in A431 cells was alleviated by Prx-LCA2 treatment, as evidenced by increased cell viability, reduced ROS levels, enhanced antioxidant enzyme activities, and decreased levels of MDA and PCG. In vivo, H2O2-induced skin oxidative damage in mice was significantly ameliorated by Prx-LCA2 treatment, including improvement in antioxidant enzyme activities and reduction in oxidative damage markers (MDA, PCG and 8-OHdG). Additionally, Prx-LCA2 increased HYP content in the skin, indicating improved collagen integrity. Histological analysis of mouse skin further confirmed the therapeutic efficacy of Prx-LCA2. The enterotoxin-derived carrier system exhibited excellent biosafety profile with no observed cytotoxicity or skin irritation. This microbial-based protein engineering strategy provides a promising platform for transdermal delivery of antioxidant therapeutics.